Photometric Calibration of the Supernova Legacy Survey Fields - Regnault, N; Conley, A; Guy, J; Sullivan, M; Cuillandre, J; Astier, P; Balland, C; Basa, S; Carlberg, R; Fouchez, D; Hardin, D; Hook, I; et al. (2009)
We present the photometric calibration of the Supernova Legacy Survey (SNLS) fields. The SNLS aims at measuring the distances to SNe Ia at (0.3